2009
DOI: 10.1007/s11265-009-0387-7
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Area, Time and Power Models for FPGA-Based Implementations

Abstract: This paper presents accurate area, time, power estimation models for implementations using FPGAs from the Xilinx Virtex-2Pro family (Deng et al. 2008). These models are designed to facilitate efficient design space exploration in an automated algorithmarchitecture codesign framework. Detailed models for estimating the number of slices, block RAMs and 18 × 18-bit multipliers for fixed point and floating point IP cores have been developed. These models are also utilized to develop power models that consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Figure 8 shows the result of comparison against Altera-OpenCL (AOCL), using a 2D SOR kernel. 10 The Tytra solution (with an AOCL shell) yields an order of magnitude better performance than the AOCL-only solution on the same FPGA.…”
Section: Performance Comparisonmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 8 shows the result of comparison against Altera-OpenCL (AOCL), using a 2D SOR kernel. 10 The Tytra solution (with an AOCL shell) yields an order of magnitude better performance than the AOCL-only solution on the same FPGA.…”
Section: Performance Comparisonmentioning
confidence: 98%
“…However, their work focuses on loop-unrolling, and is fundamentally different in terms of design entry and variant generation. Deng et al [10] present cost models based on the MATLAB-based FANTOM tool, for area, time and power. Their estimation model works on generated HDL whereas we make estimates at a higher abstraction, and our approach of generating and evaluating variants is fundamentally different.…”
Section: Related Workmentioning
confidence: 99%
“…The a n coefficient can be calculated by α =0 and b n coefficient can be calculated by α= (1/4n). Prasanna et al [5] showed that using Bruns original form, the even and odd Fourier coefficients can be computed by equations (7) and (8).Therefore, The Bruns original AFT uses the weighted s discrete values of A(t) where the weights w given as ± 1. An improved and area effici design of AFT is implemented on Xilinx Vir data flow for AFT implementation is shown in…”
Section: IImentioning
confidence: 99%
“…Although the de coefficients using the proposed meth impact on the system performance the AFT algorithm onto Xilinx FPG first computed. In order to validate also computed in Matlab using direc (7) and (8).…”
Section: Scaling Of Alternate Averagmentioning
confidence: 99%
“…The power phase measurement system is designed based on FPGA, and the results indicate it almost immune to noise of power [8]. Reference [9] develop power models that consider the effect of logic power, signal power, clock power and I/O power. With the development of technology and usage of FPGA, the power quality detect devices become more and more powerful and the measure accuracy increase quickly [10].…”
Section: Introductionmentioning
confidence: 99%